2019
DOI: 10.3390/app9071507
|View full text |Cite
|
Sign up to set email alerts
|

Low Frequency Sound Absorption by Optimal Combination Structure of Porous Metal and Microperforated Panel

Abstract: The combination structure of a porous metal and microperforated panel was optimized to develop a low frequency sound absorber. Theoretical models were constructed by the transfer matrix method based on the Johnson—Champoux—Allard model and Maa’s theory. Parameter optimizations of the sound absorbers were conducted by Cuckoo search algorithm. The sound absorption coefficients of the combination structures were verified by finite element simulation and validated by standing wave tube measurement. The experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 33 publications
0
33
0
Order By: Relevance
“…Meanwhile, when the frequency range was 100-2000 Hz, the absolute value and relative percentage of improvement of the theoretical average sound absorption coefficient fell from 0.3690 and 247.76% to 0.1050 and 15.44% respectively with thickness of the polyurethane foam increased from 10 mm to 40 mm. The major reason for this phenomenon was that sound absorption performance of the polyurethane foam in the entire frequency range was raised when its thickness rose, which was consistent with normal absorption property of the porous material [15][16][17]31,33,35]. Comparisons of theoretical data, simulation data, and experimental data of the sound absorption coefficients of the composite sound-absorbing structure are shown in Figures 9 and 10 respectively.…”
Section: Optimal Structural Parametersmentioning
confidence: 66%
See 2 more Smart Citations
“…Meanwhile, when the frequency range was 100-2000 Hz, the absolute value and relative percentage of improvement of the theoretical average sound absorption coefficient fell from 0.3690 and 247.76% to 0.1050 and 15.44% respectively with thickness of the polyurethane foam increased from 10 mm to 40 mm. The major reason for this phenomenon was that sound absorption performance of the polyurethane foam in the entire frequency range was raised when its thickness rose, which was consistent with normal absorption property of the porous material [15][16][17]31,33,35]. Comparisons of theoretical data, simulation data, and experimental data of the sound absorption coefficients of the composite sound-absorbing structure are shown in Figures 9 and 10 respectively.…”
Section: Optimal Structural Parametersmentioning
confidence: 66%
“…According to these optimal structural parameters of the composite sound-absorbing structures obtained in Section 2.2.2, finite element simulation of the sound absorption property of the composite structure was conducted in the virtual acoustic laboratory [28][29][30][31], and the constructed simulation model is shown in Figure 3. The size of the standing wave tube was 60 mm × 60 mm × 300 mm, and its front surface was treated as the acoustic source inlet for transmission of the incident sound wave.…”
Section: Finite Element Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides these common porous sound-absorbing materials [1][2][3][4][5], some novel sound absorbers have already been developed from the standard porous metal [6][7][8][9][10][11][12][13][14][15]. Bai et al [6] had attempted to improve sound absorption efficiency of the porous metal by compression, and further promote the sound absorption performance by microperforation [7].…”
Section: Introductionmentioning
confidence: 99%
“…Otaru et al [10] proposed and optimized the porous metal with a bottleneck-type structure, which obtained the the optimal sound absorption performance when its porosity was 0.68. Meanwhile, the composite structures consisted of porous metal and the other sound-absorbing materials are treated as an effective method to develop the practical acoustic absorbers for some normal or special applications [11][12][13][14][15]. Lu et al [11] had investigated influences of the microperforated panel combination on the sound absorption performance of the nickel foam, which indicated that the sound absorption coefficient was controlled by adjusting the thickness of the composite layer and location of the perforated panel.…”
Section: Introductionmentioning
confidence: 99%